IMPLEMENTASI ALGORITMA RAITA SEARCH PADA APLIKASI FILSAFAT BERBASIS ANDROID - Ratih Anggraini; Nelly Astuti Hasibuan; Suginam Suginam; Fince Tinus Waruwu (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Philosophy is the search for truth through a systematic flow of thinking, meaning that conversations about everything are carried out regularly following the prevailing system so that the stages are easy to follow. Etymologically philosophy comes from English and Greek, namely "philosophy" and "philein". This often causes difficulties to understand the meaning of the term philosophy. The term philosophy in general has a very large number so that to do the search for the meaning of the term philosophy in a philosophical book in the form of a printed book takes a long time because it must open one by one the book manually. To solve the problems described above the author builds an Android-based Philosophy application using eclipse juno. In order to simplify the search process for philosophical terms, the Raita search algorithm is implemented in the search feature contained in the Philosophy application. The raita search algorithm is a string matching algorithm with the arrangement of characters in a matched string that has the number and sequence of characters in the same string. Raita designed an algorithm by comparing the last character of the pattern starting from the far right character of the window. Android-based philosophy application that was built by the author in this study is expected to be an effective and efficient solution to get the search results of the meaning of the term philosophy in understanding the meaning of the term philosophy.Keywords: Implementation, Raita Search Algorithm, Philosophy Application, Android.